1994
DOI: 10.1021/np50103a028
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Configuration of Ecklonialactones A, B, and E, Novel Oxylipins from Brown Algae of the Genera Ecklonia and Egregia

Abstract: Ecklonialactones A, B, and E, previously isolated from the brown alga Ecklonia stolonifera, have been isolated from the Oregon phaeophyte Egregia menziesii. The structure and relative stereochemistry of ecklonialactone E were independently determined by various nmr techniques. The absolute stereochemistry of ecklonialactone A was deduced by cd analysis of a dibenzoate derivative, which indicated it possessed a 11S, 12R, 13S, 15R, 16S stereochemistry. Similar 1H- and 13C-nmr data and optical rotations for all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Interestingly, three of the same tricyclic metabolites previously reported from E. stolonifera were recently isolated by our group from the related Oregon "feather boa" kelp Egregia menziesii (both algae are classified in the order Laminariales) (65). The absolute stereochemistry of the series was established by selective opening of the epoxide at Cl3 in this latter isolate of ecklonialactone A (42), formation of the corresponding bis(p-bromobenzoate), and measurement of a negative exciton chirality in its CD spectrum.…”
Section: Ecklonialactones From Two Brown Algaesupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, three of the same tricyclic metabolites previously reported from E. stolonifera were recently isolated by our group from the related Oregon "feather boa" kelp Egregia menziesii (both algae are classified in the order Laminariales) (65). The absolute stereochemistry of the series was established by selective opening of the epoxide at Cl3 in this latter isolate of ecklonialactone A (42), formation of the corresponding bis(p-bromobenzoate), and measurement of a negative exciton chirality in its CD spectrum.…”
Section: Ecklonialactones From Two Brown Algaesupporting
confidence: 58%
“…The Oregon brown kelp E. menziesii was a source of two series of carbocyclic oxylipins which conceivably derive via an intermediate EAC, the ecklonialactones (42-44, see above) (65) and the egregiachlorides (46-48) (32). The structures of the egregiachlorides were assembled from detailed NMR study in concert with the full data sets, and relative stereochemistry was indicated by hOe results and comparison of 13C NMR spectral data with that of the ecklonialactones.…”
Section: Egregiachlorides From E Menziesiimentioning
confidence: 99%
“…Selected compounds may function as an inhibitor of LFA-1/ICAM-1 binding, expression of ICAM-1, or activation of LFA-1 [4]. On further secondary assay, six compounds, Cymathere aldehyde methyl ester (1), microcolins B (8) and C (9), avrainvilleol (12), cymopol (13) and hormothamnione diacetate (16) inhibited the direct adhesion of HL-60 cells to CHO-ICAM-1 cells through LFA-1/ICAM-1 interaction ( Table 2). Several unusual fatty acid and lipopeptide metabolites (1, 3 ± 6) inhibited cell aggregation without potent cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The green algal bromophenol avrainvilleol (12), sesquiterpene cymopol (13) and cryptophyte styrylchromone hormothamnione diacetate (16) contain polyhydroxylated phenolic moieties with lipophilic bromine or methoxylated substituents and all significantly inhibit cell-cell adhesion with similar potency (1.5 ± 2.7 mM). Interestingly, a decrease in the expression of ICAM-1 and vascular cell adhesion molecule-1 (VCAM-1) produced by chalcones and other compounds structurally related to 13 ± 16 has been reported [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation